Sorption of Radiocaesium onto Powdered and Compacted Rectorite Studied by Batch and Capillary Methods - Lei Chen; Xianjin Yu (Adsorption Science & Technology)
The sorption of radiocaesium onto Na-rectorite as a function of pH value under ambient conditions was studied by batch and capillary methods. The results indicated that the sorption of Cs + ions was dependent on the ionic strength and, to a lesser extent, on the pH value. The distribution coefficients for Cs + ion sorption onto powdered rectorite (as determined via the batch technique) were much higher than those of Cs + ions onto compacted rectorite (as determined by capillary test), thereby suggesting that the sorption of Cs + ions onto rectorite was strongly dependent on the density of rectorite, i.e. the interlaminary space of the compacted rectorite contributes significantly on Cs + ion sorption. The distribution coefficients calculated from theoretical calculations, experimental measurements and the diffusion coefficients of Cs + ions were compared and discussed in detail. The sorption and diffusion mechanisms in compacted rectorite were also discussed.